Comparing levocardia and dextrocardia in fetuses with heterotaxy syndrome: prenatal features, clinical significance and outcomes - Xiaofang Wang; Yifan Shi; Shi Zeng; Jiawei Zhou; Jia Zhou; Hongxia Yuan; Lin Wang; Weiyuan Shi; Qichang Zhou (BMC, 2017)
Abstract Background To investigate the differences in cardiovascular disease, extracardiac anomalies and outcomes between fetuses with levocardia and dextrocardia. Methods Clinical demographics, prenatal features, postnatal characteristics and the outcomes of fetuses with levocardia or dextrocardia were recorded and analyzed. Results Sixty-five fetuses with dextrocardia and thirty-eight fetuses with levocardia were enrolled. Right ventricle outlet obstruction, atrioventricular septal defect and intestinal malrotation were common in both groups. Univentricular physiology, transposition of the great arteries and esophageal atresia were more frequent in fetuses with levocardia, whereas abnormal pulmonary venous connection, double outlet of right ventricle, left ventricle outlet obstruction and brain abnormalities were more frequent in the dextrocardia group. The accuracy of evaluating cardiac malformations was high, but the sensitivity in assessing extracardiac abnormalities was low. Conclusions Although the disorders have certain overlapping features, there are several differences between fetuses with levocardia and dextrocardia. These findings might improve patient counseling and perinatal management.